If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -4) + -1(8 + -1x) = 2 + -1(5x + -9) Reorder the terms: (-4 + x) + -1(8 + -1x) = 2 + -1(5x + -9) Remove parenthesis around (-4 + x) -4 + x + -1(8 + -1x) = 2 + -1(5x + -9) -4 + x + (8 * -1 + -1x * -1) = 2 + -1(5x + -9) -4 + x + (-8 + 1x) = 2 + -1(5x + -9) Reorder the terms: -4 + -8 + x + 1x = 2 + -1(5x + -9) Combine like terms: -4 + -8 = -12 -12 + x + 1x = 2 + -1(5x + -9) Combine like terms: x + 1x = 2x -12 + 2x = 2 + -1(5x + -9) Reorder the terms: -12 + 2x = 2 + -1(-9 + 5x) -12 + 2x = 2 + (-9 * -1 + 5x * -1) -12 + 2x = 2 + (9 + -5x) Combine like terms: 2 + 9 = 11 -12 + 2x = 11 + -5x Solving -12 + 2x = 11 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. -12 + 2x + 5x = 11 + -5x + 5x Combine like terms: 2x + 5x = 7x -12 + 7x = 11 + -5x + 5x Combine like terms: -5x + 5x = 0 -12 + 7x = 11 + 0 -12 + 7x = 11 Add '12' to each side of the equation. -12 + 12 + 7x = 11 + 12 Combine like terms: -12 + 12 = 0 0 + 7x = 11 + 12 7x = 11 + 12 Combine like terms: 11 + 12 = 23 7x = 23 Divide each side by '7'. x = 3.285714286 Simplifying x = 3.285714286
| 6(x+3)/5=3x-1 | | 2x^3+9x^2+13x+6=0 | | G-8/7=8 | | -3(4x-4)+6=-12x+18 | | -5(3t-3)+3t=7t-7 | | 15y-1=15y-1 | | 2x-10=4x+14 | | 3x/5-1=2x/3+x/30 | | -4.5+z=5.8 | | 0.60x+0.25(120)=0.30(58) | | 5(x+4)-5=21-4x-6+9x | | x/5.14=-7.18 | | -1/2x=5.5 | | 6x+14y=3 | | 4x-8x+4-3= | | 3/4x-1/2=7 | | 2x^2-11x+90=0 | | y+2=-4 | | -4(3y-4)+12y= | | 13a-A-a-18A-a= | | 4x+20=8(x+3) | | -3+7(x-4)=16x+2-9x | | y+17=3y+5 | | -7x-3=-6(x+2) | | 7(-5)+2y=11 | | -2c+5c-7c= | | 8x+7=9x+10 | | y+1=-4 | | 14=a-4.5 | | 2/5b+1=4 | | 7(d-3)+10= | | 5h=35 |